2002
DOI: 10.1002/dvdy.10104
|View full text |Cite
|
Sign up to set email alerts
|

Efficient ectopic gene expression targeting chick mesoderm

Abstract: The chick model has been instrumental in illuminating genes that regulate early vertebrate development and pattern formation. Targeted ectopic gene expression is critical to dissect further the complicated gene interactions that are involved. In an effort to develop a consistent method to ectopically introduce and focally express genes in chick mesoderm, we evaluated and optimized several gene delivery methods, including implantation of 293 cells laden with viral vectors, direct adenoviral injection, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…In ovo electroporation and viral-mediated gene delivery have been successfully used for ectopic gene expression experiments that have helped illuminate the roles of overexpressed gene products during development (Logan and Tabin, 1998;Oberg et al, 2002;Colas and Schoenwolf, 2003;Stevens et al, 2003), but there are tissues that are difficult to transfect with these methods. The pegylated lipofection strategy eliminates some of the limitations and deleterious effects of electroporation or viral particles and can be used for those experiments for which electroporation and viral mediated delivery are poorly suited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovo electroporation and viral-mediated gene delivery have been successfully used for ectopic gene expression experiments that have helped illuminate the roles of overexpressed gene products during development (Logan and Tabin, 1998;Oberg et al, 2002;Colas and Schoenwolf, 2003;Stevens et al, 2003), but there are tissues that are difficult to transfect with these methods. The pegylated lipofection strategy eliminates some of the limitations and deleterious effects of electroporation or viral particles and can be used for those experiments for which electroporation and viral mediated delivery are poorly suited.…”
Section: Discussionmentioning
confidence: 99%
“…pCX-GFP was a gift from Kerby Oberg (Loma Linda University) and has been described elsewhere (Oberg et al, 2002). pCX-␤GAL was constructed by cutting the GFP gene from pCX-GFP with EcoRI, gel isolating the vector fragment, and inserting a 3,165-bp polymerase chain reaction (PCR) product with the ␤-galactosidase gene and EcoRI ends.…”
Section: Experimental Procedures Preparation Of Plasmid Dnamentioning
confidence: 99%
“…Furthermore, an inability or inefficiency to transduce genes into embryonic tissues such as limb mesenchymes has been recognized. A recent publication suggested the utility of a modified electrode which could be used for mesenchymal gene transduction to improve such inefficiency (Oberg et al, 2002). Other than electroporation, it has been demonstrated that gene transduction using recombinant retrovirus or adenovirus techniques are useful for analyzing gene functions in embryos (Kengaku et al, 1998;Rodriguez Esteban et al, 1998;Pizette and Niswander, 1999;Iba, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Since then, many functional studies based on electroporation-mediated gene transfer in chick have been published. Most of this work has been done in neural tissue (e.g., Araki and Nakamura, 1999;Megason and McMahon, 2002), but also in head ectoderm (Ogino and Yasuda, 1998), limb mesenchyme Swartz et al, 2001a,b;Oberg et al, 2002), the segmental plate (Dubrulle et al, 2001), and other tissues (reviewed in Itasaki et al, 1999;Swartz et al, 2001a; for technical overviews see Yasuda et al, 2000;Nakamura et al, 2000;Nakamura and Funahashi, 2001). Recent reports on gene silencing by electroporation of dsRNA in the neural tube (Pekarik et al, 2003) and the use of photoactivatable green fluorescent protein (GFP) for selective labelling of cells and subcellular structures (Patterson and Lippincott-Schwartz, 2002) are further landmarks indicating the immense potential of electroporation to decipher the cellular and molecular mechanisms regulating vertebrate development.…”
Section: Introductionmentioning
confidence: 99%